Material matters: exploring the interplay between natural biomaterials and host immune system - Tripathi, Alok Shiomurti; Zaki, Magdi E. A.; Al-Hussain, Sami A.; Dubey, Bidhyut Kumar; Singh, Prabhjot; Rind, Laiba; Yadav, Rajnish Kumar (Frontiers in Immunology, 2023)
Biomaterials are widely used for various medical purposes, for instance, implants, tissue engineering, medical devices, and drug delivery systems. Natural biomaterials can be obtained from proteins, carbohydrates, and cell-specific sources. However, when these biomaterials are introduced into the body, they trigger an immune response which may lead to rejection and failure of the implanted device or tissue. The immune system recognizes natural biomaterials as foreign substances and triggers the activation of several immune cells, for instance, macrophages, dendritic cells, and T cells. These cells release pro-inflammatory cytokines and chemokines, which recruit other immune cells to the implantation site. The activation of the immune system can lead to an inflammatory response, which can be beneficial or detrimental, depending on the type of natural biomaterial and the extent of the immune response. These biomaterials can also influence the immune response by modulating the behavior of immune cells. For example, biomaterials with specific surface properties, such as charge and hydrophobicity, can affect the activation and differentiation of immune cells. Additionally, biomaterials can be engineered to release immunomodulatory factors, such as antiinflammatory cytokines, to promote a tolerogenic immune response. In conclusion, the interaction between biomaterials and the body's immune system is an intricate procedure with potential consequences for the effectiveness of therapeutics and medical devices. A better understanding of this interplay can help to design biomaterials that promote favorable immune responses and minimize adverse reactions.